Pengaturan Batas Usia Perkawinan : Studi Komparatif Undang-Undang Perkawinan Negara-Negara Muslim (Indonesia dan Maladewa) - afrinald rizhan, afrinald rizhan (Islamic Civil Law Departement of Shari'a Faculty at Islamic State University of Sultan Maulana Hasanuddin Banten, 2024)
Abstract The regulation of the age limit for marriage in a country is an important factor inining the survival of marriage. The aim of this study is to find a comparison of marriage age limits in Indonesia and the Maldives. In this study the author uses a normative and comparative approach. The age limit in getting married is very important. Because marriage requires psychological maturity. The Quran and the Hadith do not specifically mention the minimum age for marriage. The commonly known requirement is to be well-informed, well-conscious, able to distinguish between good and bad so that it can give consent to marriage, until the time of a person to marry (buluq an-nishah), with the word